12 Post-ischemic myocardial remodeling and its modulation by an elastin-like recombinamers-based hydrog el. (16th October 2019) - Da Costa, M; Contessotto, P; Orbanic, D; Jin, C; Owens, P; Karlsson, N; Rodriguez-Cabello, JC; Dockery, P; Kilcoyne, M; Pandit, A
Abstract : Heart failure caused by myocardial infarction (MI) is a burgeoning clinical problem. The modulation of post-ischemic remodelling after MI may ameliorate the deleterious effect of myocardial infarction on cardiac function. Elastin is a main component of the cardiac ECM and has critical functions in vasculature structures. We hypothesized that an elastin-like recombinamer-based (ELRs) hydrogel could benefit post-ischemic remodelling in an ovine model of MI. A novel ovine model of MI was developed to mimic patchy regional myocardial infarction often seen at coronary revascularization surgery early after NSTEMI (Non-ST Elevation Myocardial Infarction). Interventions were performed at seven days post-MI. One group was treated with the ELR hydrogel (n=6) and the other left untreated (n=6). All animals were sacrificed three weeks after intervention, after approval by the respective Institutional Ethics Committee. Functional data of ejection fraction (EF) and Fractional Shortening (FS) were obtained using transthoracic echocardiography prior to the induction of MI, one week later prior to intervention, and at three weeks after intervention prior to sacrifice. Masson's Trichrome, anti-CD31 antibody and GS-I lectin were used for histology (n=5). Samples were analysed by confocal Raman microscopy (n=4). Fluorescent-labelled membrane proteins were incubated on a 48-lectin microarray (n=4) and were analysed by N-glycomics (n=6). RNA-sequencing was performed using an Illumina-HiSeq platform (n=3–4). A consistent average decrease in ejection fraction (EF) by 10.8%, 8.3% and 9% was seen seven days post-MI in MI-only, PBS and ELRs-hydrogel groups, respectively, with no significant difference across the groups (P=0.74). Remarkably, the decrease in EF due to MI was reversed only in the ELRs-treated group, which showed a statistically significant 16.2% average improvement (P<0.05) 21 days after the injection time. In contrast, EF in PBS-injected and MI-only groups did not improve from day seven post-MI (-2.6% and -0.3%, respectively). In addition, fractional shortening also significantly improved (P<0.05) in the ELRs-hydrogel group. Histology and confocal Raman showed a decreased fibrosis in ELRs-hydrogel-treated hearts. Enhanced angiogenesis was also observed three weeks after hydrogel injection. GS-I+/CD31+ capillaries increased from 44±18 in MI-only to 187±47 in ELRs-hydrogel-treated group (P<0.05, n=5), consistent with an angiogenic response due to the migration of endothelial cells. RNA-sequencing data showed persistence of VEGF and HGF signalling pathways only in the ELRs-hydrogel group. N-glycomics validated higher levels of terminal α-galactose associated with angiogenesis. This study demonstrates that ELRs-hydrogel treatment induced an extended healing environment after MI, characterised by reduced fibrosis and neoangiogenesis as a result of migration of endothelial cells into the area. This is possibly mediated by persistent VEGF and HGF signalling pathways, and higher levels of terminal α-galactose which is associated with angiogenesis. The result is significantly improved cardiac function in the ELRs-hydrogel-treated group. Revascularization after NSTEMI does not restore damaged myocardium. ELRs-hydrogel treatment may serve as an adjunct to revascularization by positively remodeling areas of myocardial infarction and significantly restores previously lost cardiac function.